Case Report Forensic Analysis of Foreign Object Sodomy Injuries in Children - Agatha Clarice Natalie; Liauw Djai Yen; Theresia Widyakirana Noviandewi; Sarah Stephanie Br. Ginting; Maximillian Aritonang (Jurnal Forensik dan Medikolegal Indonesia, 2026)
Sexual violence against children, particulary involving anal penetration with foreign objects, constitutes a form of extreme violence with significant physical consequences. This case report present forensic findings on a 3-year-old boy who was sodomized using a foreign object such as a toilet brush, accompanied by other physical violence resulting in death. External examination showed extensive burns, purplish bruises on the entire anal wall, and linear abrasions at the 6 o'clock position, which are characteristic of blunt trauma caused by a foreign object. This finding differs from injuries caused by genital penetration, which are generally lighter and more homogeneous. Injuries caused by foreign objects are deeper and more complex, especially in children who still have fragile perianal anatomical structures. Forensic evaluation plays a crucial role in identifying the type of violence, the tools used, and supporting the legal process. This study emphasizes the importance of thoroughness in examining cases of child sexual violence.